Tanggung Jawab Rumah Sakit terhadap Hak-Hak Konsumen Akibat Kelalaian Medis - Yuyut Prayuti; Arman Lany; Joko Susilo; Dody Hendro Susilo; Alfiyyah Rahma; Dita Annisa Ramadhanti (Jurnal Syntax Admiration, 2024)
The purpose of the study is to the legal impact of medical accidents on the rights of patients as hospital consumers and to find out how the obligations, rights and responsibilities of hospitals to consumers of health services. This research uses normative juridical research methods, namely research that emphasizes legal science but besides that it also refers to laws and regulations and examines the rules that apply in society. The approach used is a statutory approach and an analysis approach and reviewing articles, namely by reviewing and analyzing from several literature references. The data collection technique in this study is by literature study. The data analysis technique used in this study is a systematic qualitative analysis using deductive methods by drawing conclusions from general to specific with keywords legal impact, medical accidents, hospital consumer rights. As a result, the hospital's legal responsibility to patients in the effort of medical services can be in the form of responsibility for making mistakes and omissions that cause harm not only to themselves but also to others under their supervision and responsibility for losses suffered by consumers due to negligence of hospital services.